1997
DOI: 10.1634/theoncologist.2-5-324
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Markers in Ovarian Malignancies

Abstract: Epithelial ovarian cancer is the most common ovarian malignancy. CA125, the glycoprotein defined by the antibody OC 125, is the most important clinical marker for the diagnosis, treatment and follow‐up of epithelial ovarian cancer. However, like most tumor markers, it is neither wholly specific nor sensitive for the disease. We discuss how CA125 in combination with other tests can be used in the differential diagnosis of pelvic masses and as part of the investigations for cancer screening. CA125 is an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Besides tumor markers could be raised by non-malignant conditions as well as other malignancies [6][7][8]. Cancers of the lung, pancreas, colorectal, breast and non-Hodgkin's lymphomas are associated with a rise in CA125 [9,10] which is also raised in benign conditions such as endometriosis, ovarian cyst, leiomyoma uteri and pelvic inflammatory disease [4,8,11]. Only 50% of early OC is associated with raised CA125 making it unreliable for early diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Besides tumor markers could be raised by non-malignant conditions as well as other malignancies [6][7][8]. Cancers of the lung, pancreas, colorectal, breast and non-Hodgkin's lymphomas are associated with a rise in CA125 [9,10] which is also raised in benign conditions such as endometriosis, ovarian cyst, leiomyoma uteri and pelvic inflammatory disease [4,8,11]. Only 50% of early OC is associated with raised CA125 making it unreliable for early diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…CA125, a glycoprotein defined by reactivity with the antibody OC125 (Bast et al, 1981), is considered the most important serum marker in the diagnosis, treatment, and follow-up of epithelial ovarian carcinoma. However, like other markers, CA125 has limited diagnostic specificity, and can be elevated in malignant or nonmalignant disorders associated with ascites or pleural effusions (Eagle & Ledermann, 1997). Topalak et al (2002) reported that the serum CA125 level was significantly higher in patients with ascites than in those with pleural effusion, whether of benign or malignant origin.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The model suggests that HGSOC exists in an occult asymptomatic form for 3 to 4 years, where it is too small to be detected by a secreted biomarker, magnetic resonance imaging, computed tomography, and probably ultrasound, followed by a rapid growth phase in years 4 to 5 with concomitant presentation of symptoms, at which time the tumor is already metastatic and lethal. 7,8 Emerging consensus suggests that a significant fraction, perhaps over 50%, of HGSOC actually originates in the fallopian tube with subsequent migration to the ovary and peritoneum. 9,10 If this hypothesis is correct it opens a window on early detection of the disease through minimally invasive endoscopy using relatively inexpensive but robust optical components.…”
Section: Introductionmentioning
confidence: 99%